Policing the Frontier : An Ethnography of Two Worlds in Niger - Göpfert, Mirco, 1984- (Book collections on Project MUSE., 2020)
"This book explores what it means to be a gendarme investigating cases, writing reports, and settling disputes in a rural community in Niger and also addresses the irresolvable tension between bureaucratic forms and peoples' lives"--